Escitalopram should be investigated in anorexia nervosa: Rationale and review of mechanisms. (September 2022) - Strumila, Robertas; Lengvenyte, Aiste; Olie, Emilie; Courtet, Philippe; Guillaume, Sebastien
One of the biggest ambitions in the field of anorexia nervosa (AN) research is to find a reliable and effective pharmacological treatment. The fact that currently no pharmacological treatment is safe and effective in this disease is worrying and also challenging. On the basis of the progress in our understanding of AN neurobiology, we propose that escitalopram, a widely available drug, might be a safe and effective option that needs to be investigated. Escitalopram is the only selective serotonin reuptake inhibitor, without any catecholaminergic effect. As studies have shown decreased serotonergic and increased dopaminergic transmission in AN, we hypothesized that an ideal drug for AN management should boost serotonin levels to increase serotonergic and decrease dopaminergic transmission, the two main features of escitalopram action. Here, we present a short overview of pharmacological research in AN and discuss the theoretical rationale for escitalopram use in AN. We also call for double-blind, randomized, placebo-controlled trials to test whether this theoretical framework translates into clinical efficacy.